111k views
3 votes
-840=-15(-7x+7) Please help

User Iridium
by
6.1k points

1 Answer

2 votes

We move all terms to the left:
-840-(-15(-7x+7))=0

We calculate terms in parentheses: -(-15(-7x+7)), so:
-15(-7x+7)
We multiply parentheses
105x-105
Back to the equation:
-(105x-105)

We get rid of parentheses
-105x+105-840=0
We add all the numbers together, and all the variables
-105x-735=0
We move all terms containing x to the left, all other terms to the right
-105x=735
x=735/-105
x=-7
User Stuckatzero
by
6.4k points